Annealing and plasma treatment effect on structural, morphological and topographical properties of evaporated β-In2S3 films. (20th January 2020) - Rasool, S; Saritha, K; Reddy, K T Ramakrishna; Tivanov, M S; Gremenok, V F; Zimin, S P; Pipkova, A S; Mazaletskiy, L A; Amirov, I I
Abstract: Indium sulfide (In2 S3 ) is a wide bandgap semiconductor, which is widely used as a window/buffer layer in thin film solar cell applications. In2 S3 thin films were deposited using thermal evaporation technique and were annealed in sulfur ambient at 200 °C and 250 °C. Further, these films were treated in inductively coupled argon plasma sputtering with an average argon ion energy of 75 eV for 30 s. The paper presents the effect of Ar-plasma treatment on structure, elemental composition, morphology and topography of In2 S3 films and the results were reported. Further, the optimized In2 S3 layers were continued for plasma etching process with an average argon ion energy of 25 eV to study the effect of plasma etching duration on the growth of metallic indium nanoparticles over the film surface and the results were discussed in detail.